Commercial amniotic membrane extract eye drops for canine SCCED: a retrospective clinical evaluation - Luo, Jing Wen; Zhou, Zhen Lei (Frontiers in Veterinary Science, 2025)
ObjectivesThis study aims to evaluate the efficacy of amniotic membrane extract eye drops (AMEED) in promoting the healing rate of SCCED after cotton-tip debridement (CTD) in dogs.MethodsA retrospective review was conducted on the medical records of dogs with SCCED from October 2021 to December 2024. Cases treated with AMEED following CTD (AMEED group), as well as those treated with CTD alone (CTD group), were selected for further evaluation. Data analyzed included age, sex, breed, medical therapies and procedures used, time to healing, performance of a second procedure, and complications.ResultsA total number of 20 eyes from 18 dogs were included in the analysis. Eleven eyes of 10 dogs were in the CTD group, whereas nine eyes of eight dogs were in the AMEED group. The healing rates were 27.2% (3/11) in the CTD group and 77.8% (7/9) in the AMEED group following a single CTD procedure. The mean time of healing following a single CTD procedure was 16.6 days (range: 11–21 days) in the AMEED group and 10.6 days (range: 7–14 days) in the CTD group, respectively. The longer healing time in the AMEED group may be due to more chronic cases and the presence of corneal granulation tissue compared to the CTD group. A second procedure was performed on two eyes in the AMEED group and five eyes in the CTD group that failed to heal after one procedure. For the eyes that healed in both groups, no complications were observed.ConclusionTopical therapy with AMEED is a safe and effective adjuvant treatment for canine SCCED. AMEED may be preferred in situations where more invasive procedures are less favorable.